Manajemen Kompetensi Digital Guru dalam Administrasi Pendidikan di SDN Sukarukun 01 Bekasi - Astri Ardila Susanti; Suwandi (CV. Kurnia Grup, 2026)
This study aims to analyze the management of teachers’ digital competence in educational administration at SDN Sukarukun 01 Bekasi. The study employed a qualitative approach with a field research design using in-depth interviews with the principal and teachers. The findings reveal that the management of teachers’ digital competence has been implemented through planning, organizing, actuating, and controlling functions; however, it has not been conducted optimally and systematically. In the planning aspect, policies related to digital competence development remain informal and undocumented. In organizing, an informal peer collaboration pattern emerges as an adaptive strategy, where digitally competent teachers assist others. In actuating, the implementation of digital-based administration has been carried out but still faces challenges, including limited digital literacy, low self-confidence, and generational digital gaps. Meanwhile, controlling is conducted through work evaluation but lacks measurable performance indicators. The novelty of this study lies in identifying informal collaboration and generational gaps as key factors influencing the management of teachers’ digital competence. The study implies the need for strengthening formal policies, continuous training programs, and needs-based mentoring systems to enhance teachers’ digital competence effectively.